Tongshu capsule down-regulates the expression of estrogen receptor α and suppresses human breast cancer cell proliferation. - Chengzhi Du (PLoS ONE, 2014)
The Tongshu Capsule (TSC) is a prevalent form of traditional Chinese medicine widely used for its purported effects in treating mammary gland hyperplasia and inflammation. Though successful in several clinical studies, there is no clear evidence as to why TSC has a positive treatment effect, and little known about underlying mechanism that may account for it. In this study, we examined the effects of TSC and found that it has a comparatively strong growth inhibition on ERα positive breast cancer cells. TSC seems to cause G1 cell cycle arrest instead of apoptosis. Interestingly, TSC also down-regulated the expression of ERα and Cyclin D1. Consistently, TSC suppressed E2 mediated ERα downstream gene expression and cell proliferation in ERα positive breast cancer cell lines MCF7 and T47D. Depletion of ERα partially abolished the effects of TSC on the decrease of Cyclin D1 and cell viability. Our findings suggest that TSC may have therapeutic effects on ERα positive breast cancers and moreover that TSC may suppress breast epithelial cell proliferation by inhibiting the estrogen pathway.